2010
DOI: 10.1007/s12020-010-9422-5
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pheochromocytoma: predictive factors of malignancy and clinical course in 16 patients at a single tertiary medical center

Abstract: Metastases appear in approximately 10% of patients with pheochromocytoma. There is no predictive marker of malignancy. The aim is to describe clinical course of patients with malignant pheochromocytoma and to identify predictive features of malignancy. The method involves retrospective analysis of patients files diagnosed with malignant pheochromocytoma at our institution between January 1, 1980 and December 31, 2008. We identified 16 patients with malignant pheochromocytoma. There were more men than women (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 32 publications
3
60
0
3
Order By: Relevance
“…The study data of Szalat et al (Szalat et al, 2011) supported Thompson's data. Similarly, Strong et al concluded that PASS scoring system was definitely significant in pointing out malignancy, and confirmed with PASS> 4 of their malignant cases, while PASS <4 of benign cases (Strong et al, 2008).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The study data of Szalat et al (Szalat et al, 2011) supported Thompson's data. Similarly, Strong et al concluded that PASS scoring system was definitely significant in pointing out malignancy, and confirmed with PASS> 4 of their malignant cases, while PASS <4 of benign cases (Strong et al, 2008).…”
Section: Discussionsupporting
confidence: 65%
“…Yet again, this scoring system was evaluated also by Amit Agarwal et al (Agarwal et al, 2010). Numerous studies reported that the PASS system would be beneficial in differentiating tumors for having a potential to behave biologically aggressive (PASS >or=4) or benign (PASS <4) (Strong et al, 2008;Agarwal et al, 2010;Szalat et al, 2011;de Wailly et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] The pooled incidence of malignant PGL, defined as the presence of metastases, [17][18][19] in populations comprising both unaffected SDHD variant carriers and SDHD variant carriers with manifest nonmalignant PGL is about 8%. 20 Prognosis in malignant PGL is poor, with reported 5-year survival rates of 20-55% for malignant sPGL and PCC 21,22 and 60% for malignant HNPGL, 23 although a few cases of survival for 420 years after diagnosis have been described. 24,25 An increasing number of SDHD variant carriers are now being identified through (presymptomatic) testing of family members of SDHD variant carriers with manifest disease, that is, index cases.…”
Section: Introductionmentioning
confidence: 99%